PORT-LOGISTICS SERVICE LEVEL: COMPARATIVE STUDY OF THE PORTS OF RIO GRANDE AND ITAPOÁ FOR EXPORTS OF AUTO PARTS PRODUCED IN THE STATE OF RIO GRANDE DO SUL (Gestão & Regionalidade, 2023)
Today's world has shown itself to be increasingly connected, with interdependent economies and displaced production processes dependent on global supply chains. For this production system to work, ports are of outstanding importance, representing links that can contribute to the companies' competitiveness. Given this context, this study presents a comparative analysis of the ports of Rio Grande and Itapoá for the export of auto parts produced in southern Brazil. Considering the main criteria related to the evaluation of port-logistics service level found in the literature, a survey with managers of auto parts export companies located in the State of Rio Grande do Sul was carried out. The collected data were analyzed using descriptive statistical procedures and multiple regression analysis. The results indicated port costs and port efficiency as statistically significant criteria. Together, these criteria were able to explain 55.9% of the general assessment of the Port of Rio Grande compared to Itapoá, constituting critical factors for the competitiveness of these two ports from the respondents' perspective.
Keywords: Exports; Auto parts industry; Port-Logistics Service Level; Southern Brazil